The Mode of Enunciation in Beckett’s Plays - Oliven, Rafael Campos (Aletria: Revista de Estudos de Literatura, 2024)
This article analyses the question of language and its mode of enunciation as it is worked out as something that permeates the construction of the characters in Samuel Beckett’s three main plays: Waiting for Godot, Happy Days and Endgame. It therefore resorts to the analysis of language as containing the approach of the Other that can be understood as the unconscious. Authors such as Theodor W. Adorno and Michael Worton are addressed as they examine the philosophical aspects of the plays and the intersections between nonverbal language and a silent reading of them. The dilemmas of the characters in the three plays, similar to those of modern and contemporary individuals, are analyzed in the context in which the Theatre of the Absurd is inserted. It concludes that Beckett’s use of language reflects new identities that are being formed as it questions reality in its engagement with discourse and the present.